Overexpression of tissue microRNA10b may help predict glioma prognosis. (July 2016) - Zhang, Xinxin; Cheng, Jian; Fu, Ling; Li, Qingshui
Highlights: Expression of miR-10b was significantly higher in glioma than normal tissues. Overexpression of miR-10b was an independent prognositic factor for glioma. MiR-10b was related to poor overall survival in high grade glioma patients. Abstract: We investigated the relationship between microRNA-10b (miR-10b) expression and prognosis in human glioma patients. Quantitative real-time polymerase chain reaction (qRT-PCR) analysis was used to characterize the expression patterns of miR-10b in 128 glioma and 20 normal brain tissues. Clinical information – age, sex, Karnofsky Performance Status (KPS) and World Health Organization (WHO) grade – were also collected. The associations between miR-10b expression and the clinicopathological factors and outcome of glioma patients were statistically analyzed. Expression levels of miR-10b in glioma tissue were significantly higher than in normal brain tissue (P < 0.001). High-grade glioma (WHO grade III and IV) had much higher miR-10b expression levels than low-grade tumors (WHO grade I and II). Additionally, the increased miR-10b expression in the glioma tissues was significantly associated with a low KPS (P = 0.03). Kaplan–Meier survival curves and Cox regression analyses showed that overexpression of miR-10b (P = 0.01) and high grade (P = 0.02) were independent factors predicting poor outcome for glioma patients. Furthermore, subgroup analyses showed that the miR-10b expression level was significantly associated with poor overall survival in glioma patients with high grades (P < 0.001). Up-regulation of miR-10b may have value in predicting clinical outcome in glioma patients, particularly for those with high pathological grades.